UMP strategic relationship with cluster schools, Velionne Racing makes the country proud - Ahmad Razlan, Yusoff (2021)
PEKAN, 8 June 2021 - Universiti Malaysia Pahang (UMP) strategic network with cluster schools came to fruition when the Velionne Racing team from Sekolah Menengah Sultanah Hajjah Kalsom (Malaysia) and Shanghai Pinghe Middle Schools (China) received a special jury panel recognition award in the F1 in Schools World Finals competition held online in the United Kingdom recently.